New records of Mexican Dobsonflies of the genus Corydalus Latreille (Megaloptera: Corydalidae) - Alvarez, Hugo A. (ENTOMOTROPICA, 2012)
There are few studies about the distribution of Megaloptera fauna from Mexico. In the country are present thirteen species of the Corydalidae and Sialidae families; for the genus Corydalus (Corydalidae) five species are present in certain states. It was recorded for Puebla state, the presence of Corydalus magnus, Corydalus peruvianus and Corydalus texanus. Here presents first records of Corydalus luteus and Corydalus bidenticulatus for this state; thus, all the species of Dobsonfly genus Corydalus distributed in México are present in Puebla state.